Research on the Impact of Oligopoly on the Electronics Industry and Optimization Strategies — Taking Apple, Xiaomi, and Samsung as Examples - Jiang Bingxian (SHS Web of Conferences)
This study delves into the profound impact of oligopoly within the electronics industry, with a specific focus on the market dominance exerted by Apple, Xiaomi, and Samsung. These industry giants wield significant influence, shaping market trends, consumer behavior, and the competitive landscape. Understanding the dynamics of oligopoly in this sector is crucial, as the concentration of power among these companies can lead to several critical issues. The research systematically analyzes their market control, innovation strategies, and the implications for consumer choice. It identifies key challenges, including the potential stifling of innovation, reduced competition, and increased dependency within the supply chain. To address these concerns, the study proposes a series of strategic optimizations. These include diversifying product offerings to reduce market control, increasing investment in research and development to foster innovation, enhancing product customization to meet diverse consumer needs, and improving supply chain flexibility to mitigate dependencies. These recommendations are designed to counteract the negative effects of oligopoly, promoting a more competitive and innovative industry environment. The findings of this research are of significant importance, offering valuable insights for both industry practitioners and policymakers. By addressing the challenges posed by oligopolistic markets, the study contributes to the development of more effective strategies for managing competition and innovation in the electronics industry, ultimately benefiting consumers and the market as a whole.